Association between sedentary behavior and anthropometric and metabolic profiles among adolescents - Roseane de Fátima Guimarães; Michael Pereira da Silva; Oldemar Mazzardo; Rafael Vieira Martins; Wagner de Campos (Universidade Estadual Paulista (UNESP), 2013)
The purpose of this study was to establish the association between sedentary behavior and the anthropometric and metabolic profiles within a sample group of 572 adolescents from public schools in the city of Curitiba, State of Paraná, Brazil. Approximately 8 ml of blood was drawn to measure total cholesterol (TC), LDL-c, HDL-c, triglycerides, and glucose. Stature and body mass were measured to calculate the body mass index. Information about the subjects' socioeconomic status, physical activity level, sedentary behavior, eating frequency, as well as personal information was obtained through questionnaires. Descriptive statistics, measures of central tendency and percentage score, and Binary Logistic Regression were used to obtain the odds ratio with a CI of 95% and p<0.05. Half of the girls had TC levels classified as borderline or altered, and total screen time presented a significant association between the metabolic variables analyzed in the study. We conclude that girls had TC levels less favorable than that of the boys and that screen time is associated with some metabolic variables.